2013
DOI: 10.3109/14767058.2013.806478
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in pregnancy outcomes in obese women

Abstract: Objective To estimate the effect of race on perinatal outcomes in obese women. Methods Retrospective cohort study of birth records linked to hospital discharge data for all live born singleton infants ≥37 weeks gestation born to African-American or Caucasian Missouri residents from 2000 to 2006. We excluded major congenital anomalies and women with diabetes or chronic hypertension. Obesity was defined as pre-pregnancy body mass index ≥30 kg/m2. Results There were 312 412 births meeting study criteria. 27.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 27 publications
1
49
0
Order By: Relevance
“…Thus, this study indicates that sex impacts the adverse impact of exposure to maternal obesity during gestational life with women exhibiting greater sensitivity to programmed risk relative to men following fetal exposure to maternal obesity. Race impacts perinatal outcome with risk for low birth weight increased in African American women regardless of maternal BMI (127). …”
Section: History and Etiology Of The Fetal Origins Of Cardiovascular DImentioning
confidence: 99%
“…Thus, this study indicates that sex impacts the adverse impact of exposure to maternal obesity during gestational life with women exhibiting greater sensitivity to programmed risk relative to men following fetal exposure to maternal obesity. Race impacts perinatal outcome with risk for low birth weight increased in African American women regardless of maternal BMI (127). …”
Section: History and Etiology Of The Fetal Origins Of Cardiovascular DImentioning
confidence: 99%
“…For example, maternal BMI is a better predictor of macrosomia, preeclampsia, preterm birth, and child behavior problems among European American women compared with African Americans. 17,19 Together, our results suggest that, as a measure of obesity, BMI is a less valid predictor of physiological correlates of obesity (i.e., IL-6 and CRP) as well as odds of cesarean section and infant birth weight among African American women than among European American women. These findings support the emerging evidence that BMI-derived weight classifications do not necessarily confer the same meaning in adults of different races.…”
Section: Gillespie and Christianmentioning
confidence: 74%
“…For example, African American women delivered significantly lighter babies in our study and have been found to be at increased risk for low birth weight deliveries compared with European Americans, even among women with only obesity. 19 These differences may be related to, for example, increased risk for various placental pathologies among African American versus European American women. 48,49 Therefore, it may be that, among African Americans, additional risk factors for low birth weight override the typical relationship between obesity and greater infant birth weight witnessed in other groups.…”
Section: Gillespie and Christianmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the increased incidence of preeclampsia seen in several of these studies may be because of the confounding effect of comorbid obesity [51]. At least one study observed no racial differences in the incidence of preeclampsia in an obese cohort [62]. It is likely that both social and genetic factors contribute to the apparent increased incidence of preeclampsia in Hispanic and African American women [63][64][65].…”
Section: Obstetric Disparitiesmentioning
confidence: 99%